A simple method to control the pore structure and shape of freeze-cast porous SiC ceramics. Issue 16 (November 2020) - Li, Zihe; Zhang, Zhenhu; Zhao, Weimin; Li, Xiangyu; Han, Guifang; Zhang, Jingde
Abstract: Freeze casting is a useful method for fabricating porous ceramics with controllable porosities and pore sizes by adjusting the freezing temperature and solid content. However, the pore structure is reported to be mostly lamellar. For application in catalyst supports and sensors, different pore structures are necessary. Herein, a facile method to transform the pore structure from lamellar to cellular using aqueous SiC slurry is illustrated. When increasing the freezing temperature from −80 °C to −15 °C, entrapment occurred during freezing, and consequently, the pore structure changed from lamellar to cellular. The transformation mechanism is discussed thoroughly. Samples frozen at different temperatures exhibit similar porosities but different pore shapes, mechanical properties, and specific surface areas. Models were proposed to explain this difference. This study provides a simple and effective method to tune the shape of the pore and specific surface area of ceramics simultaneously, extending application fields of freeze-cast porous ceramics.